Automation of wastewater treatment facilities (McGraw-Hill, 2007)
Designed to improve plant productivity and efficiency for increased competitiveness, this state-of-the-art WEF Manual of Practice fully examines the selection of instruments, controllers and computers, installation procedures, and sizing of final control elements." "Readers will find new chapters on the the functionality of modern process control systems that explore the hardware and software issues associated with them. The book also contains a new chapter on advanced control strategies, covering the crucial topic of energy management